1994
DOI: 10.1002/ppul.1950180604
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Bone Marrow transplantation on pulmonary function in children

Abstract: The effects of current methods of bone marrow transplantation (BMT) on pulmonary function in children have not been extensively studied. We reviewed serial pulmonary function tests (PFTs) in 25 children (median age, 9 yr; range, 4-15) who received allogeneic (n = 14) or autologous (n = 11) BMT for neoplastic diseases at The Johns Hopkins Hospital. The PFTs were obtained before BMT and at 6 months (early) and 15 months (late) after transplant. In all but 6 patients, PFTs were normal before BMT. A mild transient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 14 publications
1
52
0
1
Order By: Relevance
“…In earlier studies, in contrast, PFT were more likely to deteriorate when the recipient or donor was CMV positive 4 or when the recipient was CMV positive. 6 These discrepancies may be ascribable in part to the fact that we did not study donor CMV status.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In earlier studies, in contrast, PFT were more likely to deteriorate when the recipient or donor was CMV positive 4 or when the recipient was CMV positive. 6 These discrepancies may be ascribable in part to the fact that we did not study donor CMV status.…”
Section: Discussionmentioning
confidence: 84%
“…This improvement could be explained by a decreased carbon monoxide diffusing capacity before BMT due to recent chemotherapy and by absence of significant alteration of carbon monoxide diffusing capacity at 2 years after BMT. Five studies 4,[6][7][8][9] found a significant decrease in this variable 8-12 months after BMT, followed by partial recovery. We cannot rule out a similar pattern in our patients, as we did not study diffusing capacity early after BMT.…”
Section: Discussionmentioning
confidence: 99%
“…TBI has previously been associated with decreased lung volumes in adults, but data for children are conflicting. 6,7,[20][21][22] One reason for this may be the small sample sizes in pediatric studies and the heterogeneity with respect to TBI regimen. Single-fraction TBI has been associated with more marked decrease in lung volumes and less recovery in comparison with fractionated TBI.…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising given that many fi rst-line chemotherapeutic agents such as cyclophosphamide, methotrexate, and cytosine arabinoside have been reported to cause lung toxicity. Quigley et al 99 reported a trend late effects among survivors of childhood cancer, the evidence indicates that some treatments necessary to cure malignancy contribute to long-term pulmonary dysfunction. Individual and combined treatment exposures to radiotherapy, bleomycin, alkylating agents, HSCT, and thoracic surgery increase the risk of later lung diseases.…”
Section: Other Risk-based Factors For Lung Damagementioning
confidence: 99%
“…43,45,46,48,49,52,55,99 The most commonly reported fi nding is a restrictive ventilatory defi cit, sometimes associated with a decrease in D lco . 40,42,43,45,[47][48][49]50,51,[53][54][55]58 In a cohort of survivors of childhood hematologic malignancies after allogeneic HSCT (n 5 89), Inaba et al 62 showed progressive worsening of pulmonary function measured with forced midexpiratory fl ow (25%-75%), residual volume, TLC, and D lco during a median follow-up of 8.9 years.…”
Section: Other Risk-based Factors For Lung Damagementioning
confidence: 99%